Accuracy of prehospital triage protocols in selecting severely injured patients: A systematic review. Issue 2 (August 2017) - van Rein, Eveline A.J.; Houwert, R. Marijn; Gunning, Amy C.; Lichtveld, Rob A.; Leenen, Luke P.H.; van Heijl, Mark
Abstract : BACKGROUND: Prehospital trauma triage ensures proper transport of patients at risk of severe injury to hospitals with an appropriate corresponding level of trauma care. Incorrect triage results in undertriage and overtriage. The American College of Surgeons Committee on Trauma recommends an undertriage rate below 5% and an overtriage rate below 50% for prehospital trauma triage protocols. To find the most accurate prehospital trauma triage protocol, a clear overview of all currently available protocols and corresponding outcomes is necessary. OBJECTIVES: The aim of this systematic review was to evaluate the current literature on all available prehospital trauma triage protocols and determine accuracy of protocol-based triage quality in terms of sensitivity and specificity. METHODS: A search of Pubmed, Embase, and Cochrane Library databases was performed to identify all studies describing prehospital trauma triage protocols before November 2016. The search terms included "trauma, " "trauma center, " or "trauma system" combined with "triage, " "undertriage, " or "overtriage." All studies describing protocol-based triage quality were reviewed. To assess the quality of these type of studies, a new critical appraisal tool was developed. RESULTS: In this review, 21 articles were included with numbers of patients ranging from 130 to over 1 million. Significant predictors for severe injury were: vital signs, suspicion of certain anatomic injuries, mechanism of injury, and age. Sensitivity ranged from 10% to 100%; specificity from 9% to 100%. Nearly all protocols had a low sensitivity, thereby failing to identify severely injured patients. Additionally, the critical appraisal showed poor quality of the majority of included studies. CONCLUSION: This systematic review shows that nearly all protocols are incapable of identifying severely injured patients. Future studies of high methodological quality should be performed to improve prehospital trauma triage protocols. LEVEL OF EVIDENCE: Systematic review, level III.